Unequal burden of equal risk factors of diabetes between different gender in India: a cross-sectional analysis - Sujata (Nature Portfolio, 2021)
Abstract Many studies have supported that the burden of diabetes is shared differently by different genders due to various factors associated with it. This study aims at capturing whether women and men with a similar background, dietary and smoking habits, and biological conditions (blood pressure and body mass index (BMI)) are being affected equally or differently by diabetes. We have used cross-sectional data of NFHS-4 by covering the age group 15–49 years. Association between socio-economic background, dietary habits, biological conditions, and diabetes has been estimated using two separate multivariate logistic regression models. Results show that the overall prevalence of diabetes is higher among men (2.63%) than women (2.35%). Whereas, women belonging to urban areas (3.53%), Christian category (3.92%), richer section (3.22%), women with no schooling (2.51%), those reported never to consume pulses (2.66%) and green vegetables (2.40%) and daily consuming eggs (3.66%) and chicken or meat (3.54%) are more affected by diabetes than their men counterparts. Whereas men residing in rural areas (2.30%), belonging to the general category (3.12%), SCs (2.37%) and STs (1.72%) are more affected than their women counterparts. Results have also shown a higher prevalence of diabetes among obese men (11.46%), non-vegetarian (2.71%) and those who watch television almost every day (3.03%) as compared to their women counterparts. Regression analyses show that the richest, hypertensive, and obese women and men are significantly more likely to suffer from diabetes. This study concludes that women and men with similar socio-economic status, biological conditions, dietary and smoking habits are being affected differently by diabetes. Thus, there is a need for gender dimension in research to understand and validate the differences in the needed interventions for diabetes control in India.